WADAH AKTIVITAS KRE-AKTIF - Melissa Melissa; Sidhi Wiguna Teh (Jurusan Arsitektur dan Perencanaan, 2020)
Living and growing up in urban areas with various pressures, both from home or work/school, makes people have a higher stress level. Urban people need a space in between home (first place) and a place of work / study (second place), namely the third place. Third place is important for the people because it is a place where they can be themselves, freely channel their talents and interests, as well as socializing and maintaining fitness in the midst of the busy city. Therefore, a need rises for an architectural manifestation in the form of a third place with a creative hub to channel ideas, creativity, talents, and interests and active space to maintain fitness, socialize, and build community. Alam Sutera is a developing city that has a beautiful atmosphere and integrated transportation system so that it can support a healthy walking lifestyle. In addition, Alam Sutera is also home to various types of communities, ranging from student activity units to car lovers communities. The location of the site which is located in Alam Sutera and close to universities, offices, and residential areas makes the Cre-Active Social Hub a strategic third place and able to accommodate various needs of the third activities of the Alam Sutera community and its surroundings. Cre-Active Social Hub is designed to be a place for sustainable community development, a place in between for the people of Alam Sutera, and to make the environment mood more lively and pleasant. AbstrakTinggal dan besar di daerah perkotaan dengan berbagai tekanan, baik dari rumah maupun tempat kerja atau sekolah, membuat masyarakat memiliki tingkat stres yang lebih tinggi. Masyarakat kota membutuhkan ruang antara tempat tinggal (first place) dan tempat kerja/ belajar (second place) yaitu third place. Third place penting bagi masyarakat kota untuk menjadi tempat di mana mereka bisa menjadi diri sendiri, bebas menyalurkan bakat dan minat, sekaligus bersosialisasi dan menjaga kebugaran di tengah sibuknya kota. Oleh karena itu, muncul kebutuhan akan sebuah perwujudan arsitektur berupa third place dengan creative hub untuk menyalurkan ide, kreativitas, bakat, dan minat serta active space untuk menjaga kebugaran, bersosialisasi, dan membangun komunitas. Alam Sutera merupakan sebuah kota berkembang yang memiliki suasana asri dan sistem transportasi terintegrasi sehingga dapat mendukung pola hidup berjalan kaki yang sehat. Selain itu, Alam Sutera juga merupakan rumah untuk berbagai jenis komunitas, mulai dari unit kegiatan mahasiswa hingga komunitas pecinta mobil. Lokasi tapak yang berada di Alam Sutera dan dekat dengan universitas, kantor, dan hunian membuat Wadah Aktivitas Kre-Aktif menjadi sebuah third place yang strategis dan dapat mewadahi berbagai kebutuhan third activities masyarakat Alam Sutera dan sekitarnya. Wadah Aktivitas Kre-Aktif dirancang untuk menjadi wadah bagi pembangunan komunitas yang berkelanjutan, menjadi tempat antara bagi masyarakat Alam Sutera, serta membuat suasana semakin hidup dan menyenangkan.